Magnitude, risk factors and outcome of low birth weight babies admitted to neonatal intensive care unit of a tertiary care centre in Puducherry, India - K., Maheswari; Sharma, Neha (International Journal of Contemporary Pediatrics, 2020)
Background: This study was undertaken to know the magnitude, risk factors and outcome of LBW babies admitted in NICU in a tertiary centre. Methods: This is a hospital based, retrospective study, of LBW babies admitted to NICU of Sri Venkateshwara Medical College hospital and research centre, Puducherry, from Jan 2019 - Dec 2019. Results: About 340 babies were admitted to NICU and 56 were LBW babies, 5 were excluded and 51 LBW babies analysed. Magnitude of LBW babies, 51 (15%). Socio demographic pattern showed, IUGR (62.7%). Term IUGR (52%) and preterm IUGR (9.8%). Preterm babies (37.2%). Preterms <28 weeks of gestation (7.8%), 28-34 weeks (9.8%) and 34 to < 37 weeks (19.6%). LBW babies <1kg (7.8%), 1-1.5kg (1.9%) and 1.5 to 2.49 kg (90.1%). Male (52.9%), female babies (47%). LBW babies from rural area (62.7%), urban area (37.2%). Among the maternal risk factors, maternal anemia was common (31.3%). Elderly primi (13.7%), PROM and twin pregnancy in (9.8%) each, bad obstetric history (7.8%). PIH, APH, GDM and oligohydramnios in (3.9%) each. Rh negative pregnancy, grand multipara, teenage pregnancy, ART with hypothyroidism and unbooked pregnancy seen in (1.9%) each. Fetal distress (19.6%). Morbidity was (92.1%). Most common was jaundice (31.9%), sepsis (21.2%). Feeding difficulties (19.1%), TTNB (17%), apnea of prematurity (14.8%). Hypoglycemia and HIE in (12.7%) each. Hypothermia and HMD in (10.6%) each. Seizures in (8.5%) MAS and NEC (4.2%) each, congenital anomalies and hypocalcemia in (2.1%) and mortality in (7.8%). Extreme prematurity, ELBW with sepsis and RDS being common cause of mortality. Conclusions: Iron tablets intake, nutritional care, regular antenatal checkup, spacing pregnancy, avoidance of teenage and elderly pregnancy is important. Improving the infrastructure, manpower in NICU to manage preterm babies, when surfactant and ventilation is given.